'When you give them a Pencil they often say they're writing': Preschool Teachers' Categorisation of Written Language Work with Toddlers. Issue 1 (March 2016) - Lindstrand, Sara Hvit; Willén, Polly Björk
THE SWEDISH PRESCHOOL CURRICULUM was revised in 2010 and introduced more emphasis on literacy development for very young children. In exploring how educators approach and understand these changes to the curriculum, we drew on focus group interviews with 10 preschool teams working with toddlers. As the educators talked about their work with written language with toddlers, they identified a range of activities from their everyday practice that categorised written language in various ways. As well as reporting on what the teachers said, this paper also shows how they participated in the focus groups, showing hesitancy in some cases and using categorisations, contrasts and active voicing as they shared their perspectives. The study's findings suggest that early childhood educators would benefit from engaging more deeply in theories of literacy that align with early childhood education. This will enable them to theorise from their practice and to articulate their understandings and practice within their teams and to others.